Identification of patients and plaques vulnerable to future coronary events with near-infrared spectroscopy intravascular ultrasound imaging: a prospective, cohort study. Issue 10209 (2nd November 2019) - Waksman, Ron; Di Mario, Carlo; Torguson, Rebecca; Ali, Ziad A; Singh, Varinder; Skinner, William H; Artis, Andre K; Cate, Tim Ten; Powers, Eric; Kim, Christopher; Regar, Evelyn; Wong, S Chiu; et al.
Summary: Background: Near-infrared spectroscopy (NIRS) intravascular ultrasound imaging can detect lipid-rich plaques (LRPs). LRPs are associated with acute coronary syndromes or myocardial infarction, which can result in revascularisation or cardiac death. In this study, we aimed to establish the relationship between LRPs detected by NIRS-intravascular ultrasound imaging at unstented sites and subsequent coronary events from new culprit lesions. Methods: In this prospective, cohort study (LRP), patients from 44 medical centres were enrolled in Italy, Latvia, Netherlands, Slovakia, UK, and the USA. Patients with suspected coronary artery disease who underwent cardiac catheterisation with possible ad hoc percutaneous coronary intervention were eligible to be enrolled. Enrolled patients underwent scanning of non-culprit segments using NIRS-intravascular ultrasound imaging. The study had two hierarchal primary hypotheses, patient and plaque, each testing the association between maximum 4 mm Lipid Core Burden Index (maxLCBI4mm ) and non-culprit major adverse cardiovascular events (NC-MACE). Enrolled patients with large LRPs (≥250 maxLCBI4mm ) and a randomly selected half of patients with small LRPs (<250 maxLCBI4mm ) were followed up for 24 months. This study is registered with ClinicalTrials.gov, NCT02033694 . Findings: Between Feb 21, 2014, and March 30, 2016, 1563 patients were enrolled. NIRS-intravascular ultrasound device-related events were seen in six (0·4%) patients. 1271 patients (mean age 64 years, SD 10, 883 [69%] men, 388 [31%]women) with analysable maxLCBI4mm were allocated to follow-up. The 2-year cumulative incidence of NC-MACE was 9% (n=103). Both hierarchical primary hypotheses were met. On a patient level, the unadjusted hazard ratio (HR) for NC-MACE was 1·21 (95% CI 1·09–1·35; p=0·0004) for each 100-unit increase maxLCBI4mm ) and adjusted HR 1·18 (1·05–1·32; p=0·0043). In patients with a maxLCBI4mm more than 400, the unadjusted HR for NC-MACE was 2·18 (1·48–3·22; p<0·0001) and adjusted HR was 1·89 (1·26–2·83; p=0·0021). At the plaque level, the unadjusted HR was 1·45 (1·30–1·60; p<0·0001) for each 100-unit increase in maxLCBI4mm . For segments with a maxLCBI4mm more than 400, the unadjusted HR for NC-MACE was 4·22 (2·39–7·45; p<0·0001) and adjusted HR was 3·39 (1·85–6·20; p<0·0001). Interpretation: NIRS imaging of non-obstructive territories in patients undergoing cardiac catheterisation and possible percutaneous coronary intervention was safe and can aid in identifying patients and segments at higher risk for subsequent NC-MACE. NIRS-intravascular ultrasound imaging adds to the armamentarium as the first diagnostic tool able to detect vulnerable patients and plaques in clinical practice. Funding: Infraredx.